KEBAN BARAJ GÖLÜ'NDEN YAKALANAN MASTACEMBELUS MASTACEMBELUS (BANK VE SOLANDER 1794) KARACİĞERİNİN HİSTOLOJİK OLARAK İNCELENMESİ - KAYA, BÜŞRA (Fırat Üniveristesi, 2019)
Bu çalışmada; Elazığ Keban Baraj Gölü'nden temin edilen 5 adet Mastacembelus mastacembelus (Bank and Solander, 1794) karaciğerinin histolojik yapısı ışık mikroskobunda incelendi. Karaciğer, M.mastacembelus'un büyük iç organıdır. Periton boşluğunu perikart boşluğundan ayıran transversa septumuna yakındır. Anatomik olarak karaciğer bir lobdan oluşur. Karaciğer başlıca histolojik bileşenlerden oluşur. Parankimi hepatositleri içerir. Çevredeki glisson kapsülünün devamı olan stromanın bağ dokusu kollajendir. Santral venleri oluşturan endotel hücreleri, az miktarda bağ dokusu ile çevrilidir. Karaciğerin toplam hücre yoğunluğunun büyük kısmını büyük ve poligonal şekilli hepatositler oluşturmaktadır. Bu hücreler tek ya da iki çekirdek içermektedir. Glikojen depoları bulunmaktadır. Hepatositler arasında kılcal damar olan sinüzoidler bulundu. Sinüzoidler hematoksilen eosin boyamasında, hepatositler arasında soluk pembe olarak görüldü. Hepatositler ve sinüzodler arasında disse aralığı (perisinusoidal) mevcuttu. Ayrıca, sinüzoidler, oval çekirdeği içeren kuppfer hücresi denilen spesifik bir hücre tipi içermektedir. Safra kanalları, küboidal veya kolumnar epitel hücreleri nedeniyle kan damarlarından kolayca ayırtedilmektedir. Karaciğerde hepatik arter ve hepatik portal ven bulunmaktadır. Bu damarların etrafında ise bağ doku lifleri çevrilidir.

In this study, the histological structure of liver of five Mastacembelus mastacembelus (Bank and Solander, 1794) obtained in Keban Dame Lake were examined in the light microscope. The liver is the large internal organ of the M.mastacembelus body. it is close to the transversa septum which seperates the peritoneal cavity from the pericardial cavity.. Anatomically the liver consists of one lobes. The liver consists of the major histological components. Parenchyma, which is represented by hepatocytes. Stroma consists of connective tissue and contains the vessels. It which is a continuation of the surrounding capsule of Glisson. It the connective tissue of the stroma is collagen. The endothelial cells forming the central veins are surrounded by a small quantity of connective tissue fibers. Sinusoids, which are capillaries travelling between hepatocytes. The sinusoids appear as pale spaces between the hepatocytes in hematoxylin and eosin (H&E) staining. Spaces of Disse (perisinusoidal), which are located between the hepatocytes and the sinusoids. In addition, sinusoids contain a specific cell type called kupffer cell, containing ovoid nuclei. Hepatosit are large and polygonal shape cells make up most of the total cells of the liver. They can contain between one and two nuclei, which are large and spherical. These cells has got Glycogen deposits. The ducts of the biliary are easily distinguished from blood vessels by the lining of cuboidal or columnar epithelial cells. There are hepatic artery and hepatic portal vein in the liver. The endothelial lining of the sublobular veins is surrounded by a high quantity of connective tissue fibers, consisting of a layer of both collagenous and elastic fibers.
Histological examination of mastacembelus mastacembelus (Bank ve Solander 1794) liver caughted from Keban Dam Lake
Keywords: Su Ürünleri